UPAYA MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DENGAN MENGGUNAKAN MODEL DISCOVERY LEARNING PADA MATA PELAJARAN MATEMATIKA KELAS IXA SMPN 4 TAPUNG HILIR TAHUN PELAJARAN 2019/2020 - Sri Dayanti (Journal of Education and Teaching, 2020)
This class action research aims to describe the learning outcomes of students before participating in the learning process by using the discovery learning model, class IXA SMPN 4 Tapung Hilir on mathematics learning material on the Cone Volume; describe the learning activities of students as long as students follow the learning by using the discovery learning model, class IXA SMPN 4 Tapung Hilir on the learning of mathematics material Cone Volume; describe the improvement in student learning outcomes after students follow the learning process by using the discovery learning model, class IXA SMPN 4 Tapung Hilir on mathematics learning material Cone Volume. The design set in this study is classroom action research. In class action research in general there are four stages that are commonly passed, namely planning, implementing, observing, and reflecting. The initial condition of students is when students have not received learning by using the Discovery Learning learning model. The initial data used is the data of students' daily test scores which are still low and many are incomplete from the minimum completeness criteria (KKM), which is equal to 51.72% of students not completing completeness. In the test results in the first cycle, students who reached KKM totaled 23 people with the highest score of 100 as many as 2 people and the lowest score of 65 as many as 6 people. From the results of the assessment conducted in the first cycle that is obtained a value of 65-71 with a frequency of 13 (44.84%), a value of 72-78 with a frequency of 5 (17.24%), a value of 79-85 with a frequency of 5 (17.24% ), a value of 86-92 with a frequency of 3 (10.34%), a value of 93-100 with a frequency of 3 (10.34%).